Effect of Graded Levels of Toasted Pigeon Pea [Cajanus cajan (L.) Millsp] Seed Meal Diets on Growth Performance and Carcass Characteristics of Japanese Quails (Coturnix coturnix japonica) - Yisa, A.G.; Yakubu , B.; Edache, J.A.; Danjuma, M.N.; Deme, H.I. (International Journal of Poultry Science, 2013)
A five week study was conducted to determine the effect of graded levels of toasted pigeon pea on growth performance and carcass characteristics of Japanese quail chicks. In a completely randomized design, three hundred unsexed, seven day old Japanese quails used for the study were divided into four groups of seventy five birds each. Each group was divided into three replicates of twenty five birds. Four isonitrogenous (24%CP) diets incorporating graded levels (0, 10, 20 and 30%) of toasted pigeon pea were evaluated. Average daily feed intake (18.62, 19.68, 19.58 and 20.29 g), Feed conversion ratio (4.87, 5.13, 5.36 and 5.38) and feed cost (Naira) per bird (38.34, 40.86, 41.46 and 43.57) increased (p<0.05) with increasing levels of dietary toasted pigeon pea inclusion. However, average daily weight gain (3.82, 3.83, 3.65 and 3.77 g) and dressing percentages (59.53, 61.91, 58.89 and 61.92) and percentage of breast to live weight were statistically similar (p>0.05) for all the treatments respectively. The back, wings, thighs and drumsticks were affected (p<0.05) by levels of toasted pigeon pea inclusion. By this study, pigeon pea may be included in diets of Japanese quails by not more than 10% for optimum growth and cost effective feeding.